2014
DOI: 10.1021/ac503772n
|View full text |Cite
|
Sign up to set email alerts
|

Ion Mobility–Mass Spectrometry of Lasso Peptides: Signature of a Rotaxane Topology

Abstract: Ion mobility mass spectrometry data were collected on a set of five class II lasso peptides and their branched-cyclic topoisomers prepared in denaturing solvent conditions with and without sulfolane as a supercharging agent. Sulfolane was shown not to affect ion mobility results and to allow the formation of highly charged multiply protonated molecules. Drift time values of low charged multiply protonated molecules were found to be similar for the two peptide topologies, indicating the branched-cyclic peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 46 publications
(107 reference statements)
8
55
0
Order By: Relevance
“…S1). In agreement with a previous study (33), these results are explained by thermally induced unthreading, which yields a branched-cyclic peptide with a larger cross-section and therefore a longer drift time compared with the more compact lasso peptide. This analysis also yielded a pair of peaks, indicating that the peptide can adopt multiple, distinct, and interchangeable conformations in its native state.…”
Section: Genome Mining Reveals a Novel Lasso Peptide Biosyntheticsupporting
confidence: 92%
See 1 more Smart Citation
“…S1). In agreement with a previous study (33), these results are explained by thermally induced unthreading, which yields a branched-cyclic peptide with a larger cross-section and therefore a longer drift time compared with the more compact lasso peptide. This analysis also yielded a pair of peaks, indicating that the peptide can adopt multiple, distinct, and interchangeable conformations in its native state.…”
Section: Genome Mining Reveals a Novel Lasso Peptide Biosyntheticsupporting
confidence: 92%
“…Before analysis, the samples were dissolved in 50% MeCN containing an additional 4% formic acid and 0.5% sulfolane as supercharging agent. The measurements were performed with previously described instrument settings (33).…”
Section: ϫmentioning
confidence: 99%
“…Also not reflected in the analysis presented in Figure 7 are the recent interests in characterizing natural products by IM-MS based CCS measurements. 69,116,238240 Many natural products contain complex and unusual scaffolds which motivates their study by a structurally-selective technique such as IM-MS, however, natural products are conventionally classified based on bioactivity rather than structure and as such molecules which can be considered natural products are represented in virtually all of the chemical classes delineated in this review. A similar issue is seen in metabolites (not shown) which is a classification that includes small peptides, carbohydrates and lipids.…”
Section: Ccs Coverage Over Timementioning
confidence: 99%
“…26 It has also been demonstrated that ion mobility mass spectrometry can differentiate between the threaded and unthreaded states of lasso peptides in high charge states. 27 Despite this large body of work, there is still no detailed analysis of the energetics and kinetics of lasso peptide unthreading.…”
Section: Introductionmentioning
confidence: 99%